Transcriptome Profiling and Genetic Study Reveal Amplified Carboxylesterase Genes Implicated in Temephos Resistance, in the Asian Tiger Mosquito Aedes albopictus. - Linda Grigoraki; Jacques Lagnel; Ilias Kioulos; Anastasia Kampouraki; Evangelia Morou; Pierrick Labbé; Mylene Weill; John Vontas (Public Library of Science (PLoS), 2015)
BACKGROUND:The control of Aedes albopictus, a major vector for viral diseases, such as dengue fever and chikungunya, has been largely reliant on the use of the larvicide temephos for many decades. This insecticide remains a primary control tool for several countries and it is a potential reliable reserve, for emergency epidemics or new invasion cases, in regions such as Europe which have banned its use. Resistance to temephos has been detected in some regions, but the mechanism responsible for the trait has not been investigated. PRINCIPAL FINDINGS:Temephos resistance was identified in an Aedes albopictus population isolated from Greece, and subsequently selected in the laboratory for a few generations. Biochemical assays suggested the association of elevated carboxylesterases (CCE), but not target site resistance (altered AChE), with this phenotype. Illumina transcriptomic analysis revealed the up-regulation of three transcripts encoding CCE genes in the temephos resistant strain. CCEae3a and CCEae6a showed the most striking up-regulation (27- and 12-folds respectively, compared to the reference susceptible strain); these genes have been previously shown to be involved in temephos resistance also in Ae. aegypti. Gene amplification was associated with elevated transcription levels of both CCEae6a and CCEae3a genes. Genetic crosses confirmed the genetic link between CCEae6a and CCEae3a amplification and temephos resistance, by demonstrating a strong association between survival to temephos exposure and gene copy numbers in the F2 generation. Other transcripts, encoding cytochrome P450s, UDP-glycosyltransferases (UGTs), cuticle and lipid biosynthesis proteins, were upregulated in resistant mosquitoes, indicating that the co-evolution of multiple mechanisms might contribute to resistance. SIGNIFICANCE:The identification of specific genes associated with insecticide resistance in Ae. albopictus for the first time is an important pre-requirement for insecticide resistance management. The genomic resources that were produced will be useful to the community, to study relevant aspects of Ae. albopictus biology.